PERAN STRATEGIS HUMAS PADA SEKOLAH UNGGUL BERORIENTASI STAKEHOLDER (STUDI KASUS DI SMK SUNAN DRAJAT LAMONGAN) - Dian Eka Lestari (Fakultas Agama Islam Universitas Billfath, 2019)
The relevance of education is one of the problems that until now is still difficult to find the solution. The relevance of education itself is the suitability of educational programs conducted by educational institutions with the needs of the community as users or educational stakeholders. To equip the graduates so as to meet the needs of stakeholders, the position of Vocational High School (SMK) is one of the spearheads, it is because SMK is considered able to guarantee three education domains, namely the attitude, knowledge and skills that integrated in the best education pattern so that the graduates are appropriate with the needs of the business / industry (link and match). Vocational High School of Sunan Drajat Lamongan is one of the schools that is able to provide programs that can match the needs of Lamongan stakeholders with more than 50% of their graduates are able to be accepted in Business World / Industry. This reseach aims to reveal and analyze the strategic role and impact of the strategic role of public relations in the stakeholder-oriented excellent school Vocational High School of Sunan Drajat Lamongan. This research is a qualitative type with case study approach. Data collection was done by interview and documentation method. Data analysis techniques include data reduction, data presentation, and conclusions. Checking the validity of the findings is done by crediblity method with the techniques of triangulation of sources and methods and techniques of peer discussion. The informants of this research are principal, vice principal (public relation, curriculum, student, facilities and infrastructure), head of skill competence, productive teacher, administration staff of SMK Sunan Drajat Lamongan and graduate users. The results of this study indicate that: 1) the role of stretegis of public relation of SMK Sunan Drajat Lamongan, among others are on: (a) curriculum field, (b) field of facilities and infrastructure, (c) field of student, (e) head of skill competence, (2) the impact of the strategic role of SMK Sunan Drajat Lamongan, among others are on: (a) schools, are on: (1) curriculum, (2) facilities and infrastructure, (3) student, (4) head master, (5) productive teachers and head of skill competence, (6) institution itself, (b) stakeholders, ie: (1) stakeholders know the program and the skill program developed by school, (2) the stakeholder need for labor is easy to obtain, (3) stakeholders are able to participate in the school program by providing input/suggestions related to the students' abilities and skills.